Memoirs of a Kamikaze a World War II pilot's inspiring story of survival, honor and reconciliation - Odachi, Kazuo; Ohta, Shigeru; Nishijima, Hiroyoshi (Tuttle Publishing, 2020)
This book tells the story of Kazuo Odachi who--in 1943, when he was just 16 years-old--joined the Imperial Japanese Navy to become a pilot. A year later, he was unknowingly assigned to the Kamikaze Special Attack Corps--a group of airmen whose mission was to sacrifice their lives by crashing planes into enemy ships. Their callsign was "ten dead, zero alive."